2014
DOI: 10.1177/1074248414534916
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Macrophage Subsets for Infarct Repair

Abstract: Macrophages are involved in every cardiovascular disease and are an attractive therapeutic target. Macrophage activation is complex and can be either beneficial or deleterious, depending upon its mode of action, its timing, and its duration. An important macrophage characteristic is its plasticity, which enables it to switch from one subset to another. Macrophages, which regulate healing and repair after myocardial infarction, have become a major target for both treatment and diagnosis (theranostic). The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 175 publications
(198 reference statements)
0
73
0
Order By: Relevance
“…We observed that ferumoxytol labeling caused a twofold reduction in phagocytosis whereas DEAE-Dex 1:4 labeling had no effect despite providing 10 times more iron uptake. Macrophages display a high degree of plasticity, which has led to the adoption of a simplified classification nomenclature; classical-activation (M1-like) and alternative-activation (M2-like) [26]. Because it may be important for macrophages to retain their phenotypic plasticity to exert their therapeutic effect, we investigated the effect of DEAE-Dex 1:4 labeling on BMDM phenotype via quantification of cell surface markers and gene expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that ferumoxytol labeling caused a twofold reduction in phagocytosis whereas DEAE-Dex 1:4 labeling had no effect despite providing 10 times more iron uptake. Macrophages display a high degree of plasticity, which has led to the adoption of a simplified classification nomenclature; classical-activation (M1-like) and alternative-activation (M2-like) [26]. Because it may be important for macrophages to retain their phenotypic plasticity to exert their therapeutic effect, we investigated the effect of DEAE-Dex 1:4 labeling on BMDM phenotype via quantification of cell surface markers and gene expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the majority of studies have used adherent cells from peritoneal exudates or spleen isolates [30,31]. Using the standard method for M isolation from the mouse peritoneum based on plastic adherence [22], these cultures contain at least 5-10% of non-M cells [25,32] [13,17,35]. This model has been used to answer two major questions: 1) how MSCs may modify the effect of an inductive environment; 2) whether the shift from one to another MΦ polarization state induced by the instantaneous microenvironment represents an irreversible or a reversible process.…”
Section: Discussionmentioning
confidence: 99%
“…The balance of M1 vs. M2 polarized macrophages has been shown to influence cardiac repair (56)(57)(58). Using rat and pig IR injury models, de Couto et al (59) showed that intracoronary infusion of CDC exosomes, but not inert fibroblast exosomes, reduced the number of CD68 + macrophages within infarcted tissue and modified the polarization state of macrophages.…”
Section: Macrophage Polarization By Cdc Exosomesmentioning
confidence: 99%